Pseudo-lemmatization in Croatian-English SMT - Brkic, Marija (Array, 2014)
One of the ﬁrst difﬁculties in conducting a thorough analysis of statistical machine translation involving Croatian as a morphologically rich and resource poor language is the lack of quality language resources. This paper presents results of two standard fourteen feature Croatian-English phrase-based statistical machine translation systems. Prior to building the second system a partial pseudo-lemmatization of the Croatian parts of training and test sets is made in an attempt to simplify the translation process. Besides automatic evaluation, a manual evaluation is conducted in order to gain insight into the nature of the translation differences achieved between the two systems.